Penerapan Teknik Skimming dalam Reading Test TOEFL Mahasiswa Ortotik Prostetik Poltekkes Surakarta - Noerdjanah; Sugiono; Syatibi, M. Mudatsir (Journal of Health and Therapy, 2023)
TOEFL is one of the indicators that an English learner is said to have language competence or not. In answering questions on the TOEFL, a technique or trick is needed, so that the time spent answering questions becomes more effective and efficient. One such technique is using the skimming technique. The purpose of this study is to find out whether the skimming technique is appropriate for use in the TOEFL reading test for students of the Orthotic Prosthetics Department of Health Polytechnic of Surakarta. The research method used is a quantitative experimental research method with a One group Pre and Post Test Design. The number of Orthotic Prosthetic students in semester III totaled 60 people in two classes, the sample was taken by random sampling. The TOEFL reading test consists of 50 numbers. Based on the results of the study it can be concluded that the use of skimming techniques can increase TOEFL Reading Test scores for Diploma III students of the Orthotic Prosthetics Department of the Surakarta Polytechnic of Health.